2013
DOI: 10.1111/tbed.12162
|View full text |Cite
|
Sign up to set email alerts
|

Systems Biology and Ratio-Based, Real-Time Disease Surveillance

Abstract: Most infectious disease surveillance methods are not well fit for early detection. To address such limitation, here we evaluated a ratio- and Systems Biology-based method that does not require prior knowledge on the identity of an infective agent. Using a reference group of birds experimentally infected with West Nile virus (WNV) and a problem group of unknown health status (except that they were WNV-negative and displayed inflammation), both groups were followed over 22 days and tested with a system that anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The postulates described in Figure 1 have been abundantly demonstrated (41, 44, 51, 52, 64). As shown in Figure 2C, data ambiguity may occur when structures of low complexity are used (41).…”
Section: Non-reductionist Applicationsmentioning
confidence: 91%
See 3 more Smart Citations
“…The postulates described in Figure 1 have been abundantly demonstrated (41, 44, 51, 52, 64). As shown in Figure 2C, data ambiguity may occur when structures of low complexity are used (41).…”
Section: Non-reductionist Applicationsmentioning
confidence: 91%
“…Both problems may be addressed with structures that reveal a single (one data point-wide) line of observations. Such structures eliminate variability from all dimensions—except along the line—and detect temporal changes that occur along the line, even when such changes are numerically small and/or the individuals being tested include “slow” and “fast” responders (41, 51). …”
Section: Toward Remedial Strategies (Ii): Methodological Foundationsmentioning
confidence: 99%
See 2 more Smart Citations
“…We identified 40 and 15 death-receptor and ER genes, respectively, related to liver regeneration. We also employed the gene synergy formula (Et) (Xu et al, 2012) to analyze the interactions between the genes identified above in an effort to determine the role of death receptor and ER apoptosis pathway-related genes in rat liver regeneration (Durmuş et al, 2015;Fair and Rivas, 2015).…”
Section: Introductionmentioning
confidence: 99%